scijfootankle 2018
DOI: 10.30795/2595-1459.2018.v1210
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of moderate and severe hallux valgus: 30 cases undergoing surgery using the percutaneous Chevron technique

Abstract: Objetivo: Avaliar a correção dos parâmetros radiográficos e a melhora clínica da deformidade em hálux valgo moderada e grave, tratadas pela osteotomia de Chevron percutânea. Métodos: Foram operados 26 pacientes (30 pés). Foram mensurados no pré-operatório e pós-operatório: ângulo metatarsofalangiano do hálux (MTF), ângulo intermetatarsal entre o 1 o e 2 o metatarsos (AIM), ângulo da articulação metatarsal distal (AAMD) e os escores AOFAS pré e pós-operatórios com seguimento mínimo de 6 meses. Resultados: A ida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our clinical results compared positively with previous studies in the literature in the initial postoperative scores and show that good results are maintained in the long term when compared to studies with long follow-up. 7,12,25,37,52,63…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our clinical results compared positively with previous studies in the literature in the initial postoperative scores and show that good results are maintained in the long term when compared to studies with long follow-up. 7,12,25,37,52,63…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the use of minimally invasive surgical techniques (MIS) for the treatment of hallux valgus (HV), with an increasing number of published studies including clinical series, radiologic validations, cadaveric studies, comparative studies, and technical reports on MIS techniques. 1,4,8-10,15-21,23,26-36,39-43,45,55,59-64,66,70 Five recent systematic reviews concluded that MIS is a safe and reliable technique for hallux valgus correction. 6,11,28,44,65…”
Section: Introductionmentioning
confidence: 99%
“…Its overall prevalence is 23% among individuals aged 18 to 65 years and 35% in the older population (> 65 years old). It mainly affects women, with a prevalence of 30%, compared to 13% in men (1)(2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery for correcting forefoot deformities has gained popularity worldwide in recent years. These techniques preserve soft tissues and reduce recovery time and morbidities associated with the disease process and surgical intervention (2,10,11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation